PERAN DAN TANGGUNG JAWAB PEJABAT PEMBUAT AKTA TANAH DALAM PELAKSANAAN KEGIATAN PENDAFTARAN TANAH - Suwondo, Denny; Saputra, Iksan (Jurnal Hukum, 2019)
The research objective was to determine the Roles and Responsibilities of Land Deed Making Officials in the Implementation of Land Registration Activities as well as the responsibilities of the sub-district head as land deed maker official. While the deeds he made, the approach method used in this study was juridical normative or literature law research or legal research. Doctrinal, namely legal research by examining library materials and secondary materials, which in this case relates to the roles and responsibilities of temporary land deed-making officials in organizing land registration activities. The results of the research show that the Land Deed Authorization Officer has a very important role in assisting the Head of the Land Office to register land. And because of that, it is hoped that a Land Deed Making Official has good spirit and mentality as well as professionalism in carrying out his position serving the community in making land deeds, so that a sense of security and comfort from the community can be created and the purpose of land registration itself can be realized.